Intercultural Competence and Language Mastery: Indonesian EFL Teachers' Beliefs and Practices in an International Baccalaureate Framework - Chaerunnisa, Alifia; Bachtiar, Bachtiar (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
The transformative potential of the International Baccalaureate (IB) framework in English as a Foreign Language (EFL) education emphasizes inquiry-based learning, global awareness, and intercultural competence, positioning it as a pivotal model for educational reform. This study aims to explore the beliefs and practices of Indonesian EFL teachers within the IB framework, focusing on how these educators perceive and enact their roles in fostering holistic student development. Utilizing a qualitative narrative inquiry approach, the research was conducted at a primary school in Tangerang, Indonesia, involving six EFL teachers categorized by their teaching experience. Data was collected through semi-structured interviews, classroom observations, and document analysis and were subsequently examined using thematic analysis to identify key patterns and themes. The findings reveal that EFL teachers perceive their roles as multifaceted, requiring continuous professional development, cultural integration, and creating engaging, student-centered learning environments. The teachers emphasized the importance of inquiry-based learning and critical thinking, which they see as essential for preparing students for future challenges. The study's implications underscore the need for educational policies that support ongoing teacher development and the integration of holistic, inquiry-driven curricula in EFL education. These findings contribute to the broader discourse on educational reform in Indonesia, highlighting the critical role of teacher beliefs in shaping effective pedagogical practices within the IB framework